A common grade table inspiring meaningful feedback. Issue 3 (17th July 2020) - Harrison, Frank
Abstract: The use of the 1–4 grading scale is gaining popularity as schools transition to competency‐based education. However, independent interpretations and percentage conversions have led to general confusion and sometimes outright rejection of competency‐based assessment. The first step to establish clear communication is to anchor the existing four‐point GPA scale in cognitive performance, which provides a strong framework for improved student engagement. Applied research into the learning brain is shifting classroom expectations to actively engage learners with stimulating cognitive challenges, such as synthesis and creative transfer. When the cognitive performance curve is consistently applied in the development of assessment rubrics, educators will provide stronger analytical feedback through meaningful common grades.